OPTIMIZING THE USE OF SATELLITE NAVIGATION IN TRANSPORT LOGISTICS - Ergasheva Kamola Ilhomovna; Yusupov Ulug’bek (Ta'lim innovatsiyasi va integratsiyasi, 2023)
The current stage of the development of the transport sector in our country creates the need to implement new approaches to the management of cargo flows, conduct an effective management policy at the macro and micro level, and implement its modern mechanisms in the transport and logistics sectors, as well as the use of Intelligent transport systems in the field. Currently, satellite radionavigation systems have become an integral part of human society, covering all spheres of its activity. Satellite positioning technologies are widely used in various technical systems, various types of business processes, daily life, science, education, economy and other fields.